2021
DOI: 10.1177/02692155211061222
|View full text |Cite
|
Sign up to set email alerts
|

Group-based telerehabilitation intervention using Wii Fit to improve walking in older adults with lower limb amputation (WiiNWalk): A randomized control trial

Abstract: Objective Determine efficacy of the novel WiiNWalk intervention on walking-related outcomes in older adults with lower limb amputation. Design Multi-site, parallel, evaluator-masked randomized controlled trial. Setting Home-setting in three Canadian cities. Participants Community-dwelling lower limb prosthesis users over 50 years of age. Interventions The WiiNWalk group (n = 38) used modified Wii Fit activities for prosthetic rehabilitation. The attention control group (n = 33) used Big Brain Academy: Wii Degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 40 publications
0
40
0
Order By: Relevance
“…However, walking capacity measured by timed walking distance tests demonstrated conflicting results among studies. Although a feasibility study 24 found a medium effect size on the 2-Minute Walk Test, the subsequent study 26 with a calculated sample size did not find a significant difference between the virtual reality and cognitive training group; another study 23 also reported insignificant results in the 6-Minute Walk Test. A common feature of these three studies is that none incorporated dedicated gait training components in virtual reality intervention protocol; rather, participants performed static and dynamic balance activities in front of a display.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…However, walking capacity measured by timed walking distance tests demonstrated conflicting results among studies. Although a feasibility study 24 found a medium effect size on the 2-Minute Walk Test, the subsequent study 26 with a calculated sample size did not find a significant difference between the virtual reality and cognitive training group; another study 23 also reported insignificant results in the 6-Minute Walk Test. A common feature of these three studies is that none incorporated dedicated gait training components in virtual reality intervention protocol; rather, participants performed static and dynamic balance activities in front of a display.…”
Section: Discussionmentioning
confidence: 96%
“…A total of 174 participants were included in these studies: participants in seven studies 23,24,26,27,[30][31][32] had lower extremity amputation (transfemoral, knee disarticulation, transtibial, and Van Ness amputation) and, in three studies, 25,28,29 had upper extremity amputation (transhumeral, elbow disarticulation, transradial, wrist disarticulation, and partial hand amputation). Nine studies recruited adult participants, with two 24,26 of them restricted to age older than 50 yrs; one study 27 recruited children and adolescents aged 8-18 yrs. Three studies [29][30][31] were conducted at a military medical center, three at home 24,26,27 (two of them had initial supervised sessions in a rehabilitation facility), and four 23,25,28,32 at medical and rehabilitation facilities.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, 60 outcome measures have had their psychometric properties evaluated with people with LLA. 11 Other outcome measures, including the 5 times sit-to-stand test, 12,13 the Wiifit, 14,15 and the EuroQol 5D, 16,17 which has subsequently had some validation, 18 have been used in both clinical and research settings but have not had their psychometric properties studied in this population. "…”
Section: Introductionmentioning
confidence: 99%